Role of nitric oxide on the vasorelaxant effect of atrial natriuretic peptide on rabbit aorta basal tone - Romano, Monica Liliana (2002)
The role of nitric oxide (NO) on the vasorelaxant effect of atrial natriuretic peptide (ANP) on the basal tone of rabbit aortic rings conditioned to angiotensin II (Ang II) was studied. ANP aortic relaxation and nitrite release were measured in the presence and absence of endothelium and a NO-synthase inhibitor. Ang II at 10 8 M triggered a contractile response, conditioning the vessel to a vasorelaxant effect of ANP (10 8 M). This effect was significantly enhanced by endothelium removal, NG-nitro-L-arginine methyl ester (L-NAME, 10 4 M), and methylene blue (10 5 M). ANP decrease of basal tone in Ang-II-sensitized aortic rings was improved when a higher concentration of Ang II was used (10 6 M). Basal and Ang-II-stimulated nitrite release were measured in stretched (S) and nonstretched (NS) aortic rings. Nitrite release was significantly increased in S rings (p < 0.001). L-NAME (10 4 M) partially inhibited nitrite release in both basal and Ang-II-stimulated S aortic rings. In NS aortic rings, the NO inhibitor did not inhibit basal nitrite release but blunted the Ang-II-stimulated nitrite level. A significant negative correlation between nitrite release and the ANP vasorelaxant effect on basal tone was dependent on the Ang-II-sensitizing dose. The present results demonstrate that ANP relaxant effects on aortic basal tone are related to NO levels, which are regulated by S- and Ang-II-concentration-dependent NO generation and quenching.Key words: atrial natriuretic peptide, nitric oxide, vascular reactivity, basal tone, rabbit aorta.